Anomali Sistem Presidensial Indonesia (Evaluasi Praktek Politik Parlementarian) - Sexio Yuni Noor Sidqi (Fakultas Hukum Universitas Islam Indonesia, 2008)
The combination on presidential system and multi-political parties, in its practice cannot lead to the formation of a strong government, but rather this lead to the anomaly presidential system and being trapped in the parliamentary system.